ANALISIS SUBSTRAT DI EKOSISTEM KAMPUNG NIPAH DESA SEI NAGALAWAN SERDANG BEDAGAI SUMATERA UTARA - Arum Novi Sari; E. Harso Kardhinata; Hanifah Mutia ZNA (Universitas Medan Area, 2017)
This research was conducted to determine the type of substrate and its composition in Kampung Nipah ecosystems Perbaungan Serdang Bedagai District of North Sumatra in February to March 2016. Sampling by using the pipe with descriptive methods and the purposive random sampling technique, while the measured variable is the biology variables that includes physical and chemical factors waters. Physical and chemical factors include pH, salinity, temperature. The study of these types of substrates include gravel, sand is very coarse, coarse sand, medium sand, fine sand, very fine sand, silt and clay. Measurement of physical and chemical factors waters obtained an average pH 7 both estuaries, mangrove rehabilitation and natural; salinity of estuarine waters at 200/00 and the rehabilitation of 280/00 natural mangrove 240/00; average temperature of 29-30°C. At the mouth of the river, gravel 0.95%, 97.56% sand and mud of 1.58%, obtained ma sand and mud of 1.58%, obtained mangrove rehabilitation of gravel 0.16%, 93.53% sand, and mud 6.12%, while the natural mangrove 0% gravel, sand 29.88%, 69.89% and mud. So we get the type of substrate on river estuaries nypa and mangrove rehabilitation is the sandy substrate and on a natural mangrove is a muddy substrate.